2010
DOI: 10.1007/s10165-009-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Mizoribine therapy in a patient with lupus nephritis: the association between mizoribine concentration and peritoneal dialysis

Abstract: We describe a 20-year-old female with systemic lupus erythematosus (SLE) who developed renal failure during continuous ambulatory peritoneal dialysis (CAPD). The patient was treated with mizoribine (MZR). MZR peak concentration was 1.8 mug/ml and was sufficient for clinical efficacy as measured by serological data. Treatment with MZR was safe and useful even while undergoing CAPD. Achieving optimal MZR blood concentration was important for treatment of SLE, even though the patient was in end-stage renal failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…4). Although these concentrations were lower than the suggested effective dose [20, 21], the PR3-ANCA titer was still reduced sufficiently to maintain remission of the ANCA-associated vasculitis. We do not know the exact reason for MZR’s effectiveness at the lower concentration; however, it was recently reported that 14-3-3 proteins are MZR-binding proteins [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Although these concentrations were lower than the suggested effective dose [20, 21], the PR3-ANCA titer was still reduced sufficiently to maintain remission of the ANCA-associated vasculitis. We do not know the exact reason for MZR’s effectiveness at the lower concentration; however, it was recently reported that 14-3-3 proteins are MZR-binding proteins [24].…”
Section: Discussionmentioning
confidence: 99%
“…Peak MZR blood levels of >0.66 μg/ml are effective for improving the clinical signs and symptoms of lupus nephritis [20, 21]. On the other hand, liver dysfunction and thrombocytopenia can develop at a trough level of >5 μg/ml [9].…”
Section: Discussionmentioning
confidence: 99%